HUBUNGAN KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH, KINERJA PENDIDIK DAN TENAGA KEPENDIDIKAN TERHADAP STATUS AKREDITASI DI SMK NEGERI SE-KOTA JAYAPURA - Kurniawan, Diki; Karim, Abdul (Idaarah: Jurnal Manajemen Pendidikan, 2020)
This study aims to determine the relationship of transformational leadership of school principals, performance of educators and education personnel to the status of accreditation in state Vocational Schools in Jayapura City. The city of Jayapura totaling 78. Data analysis techniques using multiple correlation, and the coefficient of determination to find out the percentage of the relationship.The results showed that there was no relationship between the transformational leadership of the principal and accreditation status, there was no relationship between the performance of educators and the status of accreditation. education, there is no relationship between the performance of the teaching staff and the status of accreditation, there is no relationship between the transformational leadership of the school principal, the performance of the teaching staff and the teaching staff with the status of accreditation.